Reabilitação robótica: desenvolvimento de um dispositivo interativo para pacientes com deficiências neuromotoras - Silva, Pedro Henrique Bueno Xavier e (Universidade Federal de São Carlos, 2023)
This work presents the development of an interactive electronic device aimed at the rehabilitation of upper limbs in patients with sequelae resulting from neurological diseases, such as stroke, Parkinson’s disease, and cerebral palsy. Given the increasing incidence of these conditions in Brazil and the debilitating consequences associated with them, the need for effective rehabilitation systems has become increasingly evident. The device employs a motion sensor, specifically an accelerometer, to monitor translational movements along three axes. Initial tests confirmed the robustness and accuracy of the system, while practical experiments demonstrated the applicability of the sensor in everyday activity scenarios, such as moving a cup across a table. The results reinforce the potential of the device as a supportive tool in neurological rehabilitation, contributing to improvements in patients’ motor control. Despite the promising advances, further investigations are required to fully exploit the potential of the proposed solution. In addition to the technical development, this study contributes to the literature by providing insights into the integration of technology and therapy in clinical contexts.
Robotic rehabilitation: development of an interactive device for patients with neuromotor disabilities
Keywords: Reabilitação de membros superiores; Doenças neurológicas; Dispositivo interativo; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA; 3. Saúde e Bem-Estar